2018
DOI: 10.1007/s00026-018-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

On Perturbations of Highly Connected Dyadic Matroids

Abstract: Geelen, Gerards, and Whittle [3] announced the following result: let q = p k be a prime power, and let M be a proper minor-closed class of GF(q)-representable matroids, which does not contain PG(r − 1, p) for sufficiently high r. There exist integers k, t such that every vertically k-connected matroid in M is a rank-(≤ t) perturbation of a frame matroid or the dual of a frame matroid over GF(q). They further announced a characterization of the perturbations through the introduction of subfield templates and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…(We refer the reader to [3] or [15] for the definitions of these matroids.) Hall, Mayhew, and Van Zwam [10, Theorem 1.2], based on unpublished work by Geelen, showed that the excluded minors for the class of near-regular matroids are U 2,5 , U √ 1-matroid of rank r and the largest simple near-regular matroid of rank r. We remark without proof that our main results here, combined with [9,Lemmas 4.14,4.16], show that Hypothesis 3.2 agrees with these known results.…”
Section: Preliminariesmentioning
confidence: 52%
See 4 more Smart Citations
“…(We refer the reader to [3] or [15] for the definitions of these matroids.) Hall, Mayhew, and Van Zwam [10, Theorem 1.2], based on unpublished work by Geelen, showed that the excluded minors for the class of near-regular matroids are U 2,5 , U √ 1-matroid of rank r and the largest simple near-regular matroid of rank r. We remark without proof that our main results here, combined with [9,Lemmas 4.14,4.16], show that Hypothesis 3.2 agrees with these known results.…”
Section: Preliminariesmentioning
confidence: 52%
“…The notion of frame templates was introduced by Geelen, Gerards, and Whittle in [5] to describe the structure of the highly connected members of minor-closed classes of matroids representable over a fixed finite field. Frame templates have been studied further in [8,14,9,7]. In this section, we give several results proved in those papers that we will need to prove the main results in this paper.…”
Section: Frame Templatesmentioning
confidence: 94%
See 3 more Smart Citations